Hubungan Aktivitas Fisik dan Asupan Nutrisi dengan Status Gizi Mahasiswa Fakultas Ilmu Keolahragaan: Hubungan Aktivitas Fisik dan Asupan Nutrisi dengan Status Gizi Mahasiswa Fakultas Ilmu Keolahragaan - Islam, Syahrizal; Manfred Mandosir, Yohanis; Sinaga, Evi (JURNAL OLAHRAGA PAPUA, 2023)
This study aims to: (1) Determine the relationship between physical activity and nutrional status in 2018 and 2019 Students of the Faculty of Sport Science Cenderawasih University. (2) Find out the relationship between intake of nutrients and nutrional status of 2018 and 2019 students of the faculty of sport science Cenderawasih University. (3) Determine the relationship between physical activity and intake of nutrients with the nutrion status of 2018 and 2019 Students of the Faculty of Sport Science Cenderawasih University. The method used in this research was correlation. The variable in this study were (1) physical activity (2) intake of nutrients (3) nutrion status. The sample of study was the Students of the Faculty of Sport Science Class of 2018 and 2019 which amounted to 48 people. The data analysis technique used normality test, and hypothesis testing used spearman rank and multiple correlation test with the help of SPSS Version 25. From the result of data analysis obtained: (1) Rank Spearman test results show a significance value of less than P= 0,049 < 0,05, meaning that the hypothesis was accepted. (2) rank spearman that result show a signifinance value more than P=0,837 < 0,05, meaning that the hypothesis is rejected. (3) the result of multiple correlations show that the significance value was more than P= 0,414 > 0,05, meaning that the hypothesis was rejected.